(untitled) (Aporia, 2017)
According to presentism, everything that exists is present. According to the truthmaker principle, for every true proposition there is a truthmaker – an entity that suffices for the truth of that proposition. According to realism about the past, there are true propositions about the past. Together these claims necessitate presently existing truthmakers for truths about the past (presentist truthmakers). Cameron (2010) argues that temporal distributional properties (TDPs) can play the role of presentist truthmakers. Corkum (2014) argues that they cannot. I argue against Corkum’s objections. In §2, I introduce, and outline the motivation for, TDPs. In §3, I show that unless TDPs are stipulated to be fundamental, as Cameron does, they can be reduced to temporal non–distributional properties, which are unable to play the role of presentist truthmakers. In §4, I argue against Corkum’s two objections to Cameron’s stipulation. Corkum’s first objection is that Cameron has no grounds on which to stipulate that TDPs are fundamental, and that the reducibility of TDPs to temporal non–distributional properties (as discussed in §3) shows that they are not. I argue that the burden of proof is not on Cameron to argue that TDPs are fundamental, but on Corkum to argue that they are not, and that to argue from the reducibility of TDPs to their non–fundamentality is to beg the question against Cameron: the reduction is only possible once their non–fundamentality is assumed. Corkum’s second objection is that if Cameron is allowed to stipulate that TDPs are fundamental in order to escape objections, then a superior alternative account is allowed to make the same move, rendering Cameron’s account redundant. I argue that the cases are asymmetric: the alternative account faces a legitimate objection whilst Cameron’s account does not.